Roles of sodium hydrosulfide and sodium nitroprusside as priming molecules during drought acclimation in citrus plants - Ziogas, Vasileios; Tanou, Georgia; Belghazi, Maya; Filippou, Panagiota S.; Fotopoulos, Vasileios; Grigorios, Diamantidis; Molassiotis, Athanassios (My University, 2015)
Emerging evidence suggests that the gaseous molecules hydrogen sulfide (H2S) and nitric oxide (NO) enhances plant acclimation to stress; however, the underlying mechanism remains unclear. In this work, we explored if pretreatment of citrus roots with NaHS (a H2S donor) or sodium nitroprusside (SNP, a NO donor) for 2 days (d) could elicit long-lasting priming effects to subsequent exposure to PEG-associated drought stress for 21 d following a 5 d acclimation period. Detailed physiological study documented that both pretreatments primed plants against drought stress. Analysis of the level of nitrite, NOx, S-nitrosoglutahione reductase, Tyr-nitration and S-nitrosylation along with the expression of genes involved in NO-generation suggested that the nitrosative status of leaves and roots was altered by NaHS and SNP. Using a proteomic approach we characterized S-nitrosylated proteins in citrus leaves exposed to chemical treatments, including well known and novel S-nitrosylated targets. Mass spectrometry analysis also enabled the identification of 42 differentially expressed proteins in PEG alone-treated plants. Several PEG-responsive proteins were down-regulated, especially photosynthetic proteins. Finally, the identification of specific proteins that were regulated by NaHS and SNP under PEG conditions provides novel insight into long-term drought priming in plants and in a fruit crop such as citrus in particular.
Keywords: Citrus; Drought stress; Plant proteomics; Priming; Sodium hydrosulfide; Sodium nitroprusside